The Effect of Visit-to-Visit Blood Pressure Variability on Renal Function in Geriatric Chronic Kidney Disease - Villagrasa-Flores, Alejandra A.; Vega-Colón, Jesús D.; Cintrón-Rosa, Fátima; Miranda-Valentín, Eric; Serrano-Rivera, Horacio; Ocasio-Meléndez, Ileana E.; Jiménez-Velázquez, Ivonne; Cangiano, Jose L. (Puerto Rico Health Sciences Journal, 2023)
Objective: The visit-to-visit variability (VVV) of blood pressure (BP) has been recognized as a risk factor for cardiovascular events and chronic kidney disease (CKD). The objective of this study is to valuate the association between the VVV of BP and changes in estimated glomerular filtration rate (eGFR) in elderly CKD patients at different stages of renal function. Materials and Methods: For 60 months, we analyzed the medical records of 105 patients with and without diabetes and hypertension. Systolic BP (SBP), diastolic BP (DBP), and pulse pressure (PP) were examined. A multivariable linear regression model was used to analyze the correlation between eGFR and the VVV of BP. Results: No differences were demonstrated between the groups in the clinical characteristics. Mean SBP and DBP were not significant between the groups, and we observed no decrease in renal function. A significant negative correlation between PP and eGFR was observed in the total CKD population with a P of .010 (95% CI: -0.20, -0.03) and a correlation coefficient of -0.11. Conclusion: Our study shows no statistical significances in terms of the VVVs of BP in any of the geriatric groups, with no significant decreases in renal function. However, we observed a significant negative correlation between PP and eGFR. We demonstrated that if a VVV of BP does not occur, there is no decrease in eGFR.